0.5 V fully differential current conveyor using bulk‐driven quasi‐floating‐gate technique. Issue 1 (1st January 2016) - Kumngern, Montree; Khateb, Fabian
Abstract : This study presents a new low‐voltage (LV) supply and low‐power consumption bulk‐driven quasi‐floating‐gate fully differential current conveyor (BD–QFG‐FDCCII) active element which is suitable for LV signal processing applications. The bulk‐driven technique is used to achieve LV supply as low as a 0.5 V and extended input voltage swing. On the other hand, the quasi‐floating‐gate technique is used to achieve high‐frequency performance. To prove the workability of the proposed circuit, new voltage‐mode biquadratic filter and fifth‐order leap‐frog low‐pass filter using BD–QFG‐FDCCIIs as active devices have been designed and illustrated in this study. The functionality of the proposed circuits is demonstrated through PSPICE simulations using Taiwan Semiconductor Manufacturing Company (TSMC) 0.18 µm n‐well complementary metal–oxide–semiconductor technology with a 0.5 V supply voltage and a power consumption of 16.1 µW.